The Influence of Investment Knowledge, Technological Advancements, and Investment Motivation on Investment Interest Among Generation Z - Mubarok, Fikri; Maelina, Nadya; Mulyatno, Roni (The Islamic Education and Multiculturalism Foundation, 2024)
This research aims to determine the partial effect of investment knowledge, investment motivation, and technological advancements on investment interest among Generation Z in the capital market. The population of this study consists of 200 students majoring in Accounting at the Faculty of Economics and Business, Swadaya Gunung Jati University, Cirebon, from the 2020 cohort. The sampling technique used purposive sampling, with a sample size of 67 students. Data collection in this research was conducted using questionnaires. Data analysis techniques involved descriptive statistical analysis and SPSS. The results of this study indicate that (1) investment knowledge influences investment interest, (2) investment motivation influences investment interest, and (3) technological advancements influence investment interest among Generation Z.